Synthesis of Silica Xerogel from Geothermal Sludge by Ultrasonic Assisted Alkali Extraction-Acid Precipitation. Issue 1 (February 2021) - Widiyandari, Hendri; Hayu Adhani, Shabrina; Subagio, Agus; Purwanto, Agus
Abstract: Geothermal sludge (GS) is a by-product of geothermal exploration. The geothermal power plant in Dieng, Central Java Indonesia, produces 165 ton/month GS with high silica content. This study reported the synthesis of silica xerogel from GS by ultrasonic-assisted alkali extraction-acid precipitation. The silica was extracted as sodium silicate solution using NaOH solution, which was then reacted with HCl to produce silica xerogel. The ultrasonication treatment was carried out after the aging process. The structure of silica xerogel was amorphous silica. The ultrasonication affected the increasing specific surface area. N2 adsorption-desorption BET characterization shows that the specific surface area was 162.334 m 2 /g before ultrasonication and increased to 302, 873 m 2 /g after 30 minutes of ultrasonication in controlled temperature at 26°C. The initial specific surface area of GS was 100.449 m 2 /g. The produced silica xerogel is a mesoporous material and have a pore size in the range of 2-12 nm.